Pathomorphological features of the structure of the uterus of fetuses from mothers with pregnancy complicated by pre-eclampsia of varying degrees of severity - V. D. Markowski; L. S. Kupriyanova (Patologìâ)
Aim. In order to determine the effect of preeclampsia (PE) of the mother on the structural pecularities of uterus of fetuses the structure of the uterus of 41 antenatally dead fetuses was studied using organometric, histologic, histochemical, morphometric and statistical methods.